Heat Stress After Pollination Reduces Kernel Number in Maize by Insufficient Assimilates - Niu, Shiduo; Du, Xiong; Wei, Dejie; Liu, Shanshan; Tang, Qian; Bian, Dahong; Zhang, Yarong; Cui, Yanhong; Gao, Zhen (Frontiers in Genetics, 2021)
Global warming increases the occurrence of high temperature stress in plants, including maize, and decreases the grain kernel number and yield. Previous studies indicated that heat stress mainly damaged pollen grains and thus lowered maize grain number. Other field studies have shown that heat stress after pollination still resulted in kernel abortion. However, the mechanism of high temperature affecting grain abortion after pollination remains unclear. Hence, this study investigated the field grown heat-resistant maize variety Zhengdan 958 (ZD958) and heat-sensitive variety Xianyu 335 (XY335) under a seven-day heat stress treatment (HT) at five days after the silking stage. Under the HT, the grain number of XY335 and ZD958 was reduced by 10.9% (P=0.006) and 5.3% (P=0.129), respectively. RNA-seq analysis showed a higher number of differentially expressed genes (DEGs) between HT and normal conditions in XY335 compared to ZD958. Gene encoding RuBPCase (ribulose diphosphate carboxylase) was downregulated by heat stress, and RuBPCase activity was significantly lowered by 14.1% (P=0.020) for XY335 and 5.3% (P=0.436) for ZD958 than CK, respectively. The soluble sugar and starch contents in the grain of XY335 were obviously reduced by 26.1% and 58.5%, respectively, with no distinct change in ZD958. Heat stress also inhibited the synthesis of grain starch, as shown by the low activities of metabolism-related enzymes. Under HT, the expression of trehalose metabolism genes in XY335 had upregulated, these genes may involve in kernel abortion at high temperature. In conclusion, this study revealed that post-pollination heat stress in maize mainly lowered carbohydrate availability for grain development and the heat-resistant variety still maintained and exhibited growth.